Market reforms, legal changes and bank risk-taking: evidence from transition economies - Yiwei Fang; Iftekhar Hasan; Katherin Marton (Bank of Finland, 2011)
The policy changes and structural reforms in transition economies over the past two decades have created exogenous variations in institutional development, which offers us an ideal natural experiment to analyse the causal effects of institutions on bank risk-taking behaviour. This paper examines a wide array of institutional reforms in respect of law and legal institutions, banking liberalization, and enterprise restructuring in privatization and corporate governance. Using a difference-in-difference approach, we find that banks financial stability has increased substantially subsequent to the institutional reforms. Further analysis suggests that the enhancement of financial stability mostly comes from the reduction of asset risk. Moreover, the effects of institutional reforms on bank risk are more pronounced for domestic banks than foreign banks. From the policy consideration, our study sheds light on the risk implications of different institutional reforms that have been characterizing transition countries.
URN:NBN:fi:bof-20140807451
Keywords: 330